3-Phenyl-1H-1,2,4-triazol-5-amine-5-phenyl-1H-1,2,4-triazol-3-amine (1/1). - Dolzhenko, Anton; Tan, G.; Koh, L.; Dolzhenko, A.; Chui, W. (Blackwell Munksgaard, 2009)
In the title compound, C8H8N4-C8H8N4, two tautomers, viz. 3-phenyl-1,2,4-triazol-5-amine and 5-phenyl-1,2,4-triazol-3-amine, are crystallized together in equal amounts. The 3-phenyl-1,2,4-triazol-5-amine molecule is essentially planar; the phenyl ring makes a dihedral angle of 2.3 (2)degrees with the mean plane of the 1,2,4-triazole ring. In the 5-phenyl-1,2,4-triazol-3-amine tautomer, the mean planes of the phenyl and 1,2,4-triazole rings form a dihedral angle of 30.8 (2)degrees. The electron delocalization of the amino group with the 1,2,4-triazole nucleus in the 3-phenyl-1,2,4-triazol-5-amine molecule is more extensive than that in the 5-phenyl-1,2,4-triazol-3-amine tautomer. The molecules are linked into a two-dimensional network parallel to (100) by N-H...N hydrogen bonds.